Estimation of Soil Salinity for Samples from Jabal Al-Akhdar, Ras Lanuf and Benghazi, Eastern Libya - سالمة جمعة زبيدة; انتصار جمعة المغيربي; عيادة البهلول أحمد; أمل جمعة سعيد (African Journal of Advanced Pure and Applied Sciences, 2026)
This study was conducted to estimate soil salinity in samples taken from Jabal Akhdar, Ras Lanuf, and Benghazi. Samples were collected at a depth of 20 cm and analyzed to measure pH, electrical conductivity (EC), total dissolved solids (TDS), moisture content, organic matter content, and carbonates and bicarbonates. The results showed that the soils in these areas are neutral to slightly acidic, with pH values ranging from 5.8 to 7, electrical conductivity values ranging from 0.254 to 0.755 dS/m, and total dissolved solids content ranging from 154 to 434 mg/L. These soils are characterized by low water retention capacity, with moisture content not exceeding 5.7%, and very low organic matter content, not exceeding 0.16%. These soils are characterized by not containing carbonate and bicarbonate salts.